Intraspecies Signaling between Common Variants of Pseudomonas aeruginosa Increases Production of Quorum-Sensing-Controlled Virulence Factors - Dallas L. Mould (American Society for Microbiology, 2020)
ABSTRACT The opportunistic pathogen Pseudomonas aeruginosa damages hosts through the production of diverse secreted products, many of which are regulated by quorum sensing (QS). The lasR gene, which encodes a central QS regulator, is frequently mutated in clinical isolates from chronic infections, and loss of LasR function (LasR−) generally impairs the activity of downstream QS regulators RhlR and PqsR. We found that in cocultures containing LasR+ and LasR− strains, LasR− strains hyperproduce the RhlR/RhlI-regulated antagonistic factors pyocyanin and rhamnolipids in diverse models and media and in different strain backgrounds. Diffusible QS autoinducers produced by the wild type were not required for this effect. Using transcriptomics, genetics, and biochemical approaches, we uncovered a reciprocal interaction between wild-type and lasR mutant pairs wherein the iron-scavenging siderophore pyochelin produced by the lasR mutant induced citrate release and cross-feeding from the wild type. Citrate, a metabolite often secreted in low iron environments, stimulated RhlR signaling and RhlI levels in LasR−but not in LasR+ strains. These studies reveal the potential for complex interactions between recently diverged, genetically distinct isolates within populations from single chronic infections. IMPORTANCE Coculture interactions between lasR loss-of-function and LasR+ Pseudomonas aeruginosa strains may explain the worse outcomes associated with the presence of LasR− strains. More broadly, this report illustrates how interactions within a genotypically diverse population, similar to those that frequently develop in natural settings, can promote unpredictably high virulence factor production.